2003
DOI: 10.1103/physrevlett.90.055509
|View full text |Cite
|
Sign up to set email alerts
|

C60Molecular Bearings

Abstract: An ultralubricated system is reported which confines a C60 monolayer between graphite plates. C60 molecules act as molecular bearings, assisted by the nanogears of six-membered carbon rings between C60 molecules and graphite, in which the mean dynamical frictional forces are zero up to a high load of 100 nanonewtons. A stick-slip rolling model with a step rotation of a C60 molecule is proposed. This ultralubricated system, very promising for the realization of nano- and micromachines, is expected to open a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 8 publications
6
81
0
4
Order By: Relevance
“…Such a rolling effect of the C 60 molecules as molecular ball-bearings was also recently confirmed by Kamiya and his colleagues. 45 They said that the system whose two graphite planes had a monolayer of C 60 sandwiched between them possessed negligible mean frictional forces due to the rolling effect of the C 60 molecules. This adds to our supposition that the C 60 films with properly controlled thickness and frictional mode could show good lubricity by way of the rolling effect of the C 60 molecules.…”
Section: Formation and Structure Of The C 60 Filmmentioning
confidence: 99%
“…Such a rolling effect of the C 60 molecules as molecular ball-bearings was also recently confirmed by Kamiya and his colleagues. 45 They said that the system whose two graphite planes had a monolayer of C 60 sandwiched between them possessed negligible mean frictional forces due to the rolling effect of the C 60 molecules. This adds to our supposition that the C 60 films with properly controlled thickness and frictional mode could show good lubricity by way of the rolling effect of the C 60 molecules.…”
Section: Formation and Structure Of The C 60 Filmmentioning
confidence: 99%
“…Recently, it has been demonstrated that fullerene serves a lubricant function, being described as a "molecular bearing" with superlubricity (42,43). Reducing the friction on joint surfaces may prevent the further development of cartilage degeneration (44).…”
mentioning
confidence: 99%
“…The order of magnitude of the position of the potential barrier, x  , is comparable to that of the atomic-scale distance between the neighboring stable AB-stacking positions within x-y plane. Here the AB-stacking registry formed between a graphite flake and a graphite substrate surface is considered (Miura et al, 2003(Miura et al, , 2004. This indicates that the peeling of the MWCNT starts when the outermost graphene sheet of the MWCNT goes over the potential barrier of the AB-stacking registry with the graphite substrate surface, as depicted in the lower part of Fig.…”
Section: Resultsmentioning
confidence: 99%